2021
DOI: 10.1002/fsn3.2416
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the impact of cornelian cherry consumption on blood lipid profiles

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Reducing TC, TG, and LDL‐C and increasing HDL‐C levels are strategies for both main and secondary CVD protection (Zodda et al, 2018). Consequently, many studies have been conducted in order to investigate alternative and complementary therapies in this field (Bahari, Taheri, Rashidmayvan, Hezaveh, et al, 2023; Ghavami et al, 2023; Mohammadi et al, 2021; Nattagh‐Eshtivani, Pahlavani, et al, 2022; Salehi‐Sahlabadi et al, 2020). The aim of the present research was to gather the results of randomized controlled studies on the effectiveness of sumac supplementation on lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing TC, TG, and LDL‐C and increasing HDL‐C levels are strategies for both main and secondary CVD protection (Zodda et al, 2018). Consequently, many studies have been conducted in order to investigate alternative and complementary therapies in this field (Bahari, Taheri, Rashidmayvan, Hezaveh, et al, 2023; Ghavami et al, 2023; Mohammadi et al, 2021; Nattagh‐Eshtivani, Pahlavani, et al, 2022; Salehi‐Sahlabadi et al, 2020). The aim of the present research was to gather the results of randomized controlled studies on the effectiveness of sumac supplementation on lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by the different described works, the consumption of C. mas fruits may benefit lipid disorders. A recent systematic review and meta-analysis of the effects of cornelian fruit supplementation on the blood lipid profile of animal studies revealed that the supplementation considerably reduced the levels of LDL, TG, and cholesterol and increased HDL levels compared to the control group [166].…”
Section: Hypolipidemic and Anti-atherosclerotic Propertiesmentioning
confidence: 99%
“…There is increasing emphasis on the utilization of natural antioxidants for this purpose, especially plant-based ones. Like antimicrobials, many of these antioxidants are secondary metabolites that can be isolated from plant materials, such as essential oils and phytochemicals, which also have health effects [39]. For instance, quercetin is a phytochemical that can be isolated from onions that exhibits strong antioxidant activity when incorporated into packaging materials [10].…”
Section: Antioxidantsmentioning
confidence: 99%